PENEGAKAN HUKUM TERHADAP KLINIK PRATAMA YANG MEMPEKERJAKAN PERAWAT TANPA SURAT TANDA REGISTRASI (Kajian Di Klinik Pratama Kab. Cilacap) - Jaka Eka Susanto (MIH Unsoed, 2018)
This study aimed to know law enforcement of clinics employing illegal nurses,and knowing that factors that tend to affect law enforcement. Law Research (Legal Research) done used this type of socio legal studies. The data sources included primary data in this study form an opinion from the respondents in this case include the parties involved directly or indirectly, namely District of health office Cilacap, and 5 clinic. While secondary data sources covered legislation, literature and official document relating to the subject matter. The result of the research is,not implemented law enforcement by District of health office Cilacap. It is seen that there is no function of Head of District Health Office Cilacap in coaching and supervision